Analisis Kepuasan Pelanggan di Saung Pak Ewok Restoran Ramah Keluarga di Jawa Barat - Rolan Sitinjak; Jesika Azura; Luluah Sabrina Putri; Dinda Marina; Annisa Salsabila Suryawan; Danish Ardian Pangest; Khoirul Aziz Husyairi; Tina Nur Ainun (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
The purpose of this study was to examine the effect of six variables on customer satisfaction with Saung Pak Ewok. Saung Pak Ewok is a popular restaurant with a family restaurant concept in West Java. The six variables considered are location, promotion, staff, price, product, and distribution. To achieve the research objectives, the research method used was convenience sampling. A total of 80 respondents were selected to participate in this study, representing a wide range of Saung Pak Ewok customers. Data was collected through various means including interviews, questionnaires, and observations. Multiple linear regression analysis was used to analyze the variables that affect customer satisfaction. This statistical technique allows researchers to identify the individual and combined effects of variables on customer satisfaction. The results showed that location, promotion, and human resources have a significant impact on customer satisfaction. Saung Pak Ewok's location, promotion, and staff quality were found to contribute positively to customer satisfaction. However, the price variable was found to have no significant effect on customer satisfaction. In conclusion, this study explains the variables that significantly influence customer satisfaction at Saung Pak Ewok. The findings highlight the importance of place and promotion in creating a positive customer experience. This research provides valuable insights for Saung Pak Ewok and other similar establishments seeking to increase customer satisfaction and improve overall business performance.